Biocontrol of Fusarium wilt of tomato by nano-extract of Trichoderma harzianum - Rahimizadeh, Mahya; Sadravi, Mehdi (The Indian Journal of Agricultural Sciences, 2020)
Fusarium wilt caused by Fusarium oxysporum f. sp. lycopersici is an important disease of tomato worldwide. The pathogen was isolated and purified from infected plants in tomato-growing greenhouses in southwest Iran during 2017. The impact of colony’s extract of four Trichoderma harzianum isolates were tested on colony growth of the pathogen in-vitro. Premium isolate colony’s extract of T. harzianum was converted to nano-product by mixing with silver-nitrate. The formation of nano-particles in this product was evaluated by dynamic light scattering, and scanning electron microscopy. The impact of nano-product was tested on colony growth of the pathogen and its EC50 was determined. Then the impact of this product and silver-nitrate was tested on the disease severity in two tomato varieties in-vivo. Colony’s extract of all four isolates of T. harzianum reduced the colony growth of the pathogen, but the effect of an isolate’s extract of T.harzianum 39 was more. Produced nano-extract had EC50441.9ppm for the pathogen. It also caused a significant reduction of the disease severity in-vivo, and its effect was more than silvernitrate alone. Potential of T. harzianum nano-extract for biological control of the disease is being reported for the first time as per our knowledge.